The effect of various intake levels of soybean oil on blood glucose and inflammation in mice - Xinli Pei (Taylor & Francis Group, 2018)
The effects of various intake levels of soybean oil on carbohydrate metabolism and inflammation in mice were studied. Mice were supplied with different diets, in which soybean oil provided 5, 10, 15, 20, 25, and 30% of total energy. Blood glucose indices, blood fat indices, inflammatory factors, and gene expression of insulin receptor substrates 1 and 2 Insulin receptor substrate 1 (IRS1) and Insulin receptor substrate 2 (IRS2) were analyzed. The results showed that higher intake of soybean oil can lead to excessive weight gain, higher levels of fasting blood glucose and serum insulin, increased levels of tumor necrosis factor-α, interleukin 6, hyper-sensitive C-reactive protein, and reduced expression of IRS1 and IRS2 mRNA. Primarily, we found that reduced intake of soybean oil led to a similar trend to that of a high soybean oil diet. The optimal intake of soybean oil, as supplied in the diet, was about 15–20%.